Patient-Centered Medical Home and Family Burden in Attention-Deficit Hyperactivity Disorder. Issue 6 (July 2015) - Ronis, Sarah D.; Baldwin, Constance D.; Blumkin, Aaron; Kuhlthau, Karen; Szilagyi, Peter G.
ABSTRACT: Objective: Attention-deficit hyperactivity disorder (ADHD) can impair child health and functioning, but its effects on the family's economic burden are not well understood. The authors assessed this burden in US families of children with ADHD, and the degree to which access to a patient-centered medical home (PCMH) might reduce this burden. Methods: We conducted cross-sectional analyses of 2005–2006 and 2009–2010 National Surveys of Children with Special Health Care Needs, focusing on families of children with ADHD. They defined family economic burden as (1) family financial problems (annual expenses for the child's health care or illness-related financial problems for the family) and/or (2) family employment problems (job loss, work time loss, or failure to change jobs to avoid insurance loss). Relative risk models assessed associations between PCMH and family economic burden, adjusted for child age, sex, ethnicity, ADHD severity, poverty status, caregiver education, and insurance. Results: In 2009, 26% of families reported financial problems because of the child's ADHD, 2.1% reported out-of-pocket expenses >5% of income, and 36% reported employment problems. Only 38% reported care that met all 5 criteria for a PCMH (similar to rates in 2005–2006). In multivariable analysis, care in a PCMH was associated with 48% lower relative risk (RR) of financial problems (RR = 0.52, p < .001) and 36% lower relative risk of employment problems (RR = 0.64, p < .001). Among PCMH components, family-centered care and care coordination were more strongly associated with lower burden. Conclusions: The economic burdens of families with ADHD are significant but may be alleviated by family-centered care and care coordination in a medical home.